Assessing Early Warning Systems How Have they Worked in Practice? - Berg, Andrew (International Monetary Fund, 2004)
Since 1999, the IMF''s staff has been tracking several early-warning-system (EWS) models of currency crisis. The results have been mixed. One of the long-horizon models has performed well relative to pure guesswork and to available non-model-based forecasts, such as agency ratings and private analysts'' currency crisis risk scores. The data do not speak clearly on the other long-horizon EWS model. The two short-horizon private sector models generally performed poorly